2021
DOI: 10.1556/2006.2020.00097
|View full text |Cite
|
Sign up to set email alerts
|

Work addiction and personality: A meta-analytic study

Abstract: BackgroundDuring the past three decades, research interest in work addiction has increased significantly. Most definitions concerning work addiction have specifically contained personality-related elements. However, the results of empirical studies concerning personality and work addiction are both few and mixed. The aim of the present study was to explore the role of personality in the background of work addiction.MethodsThe present study systematically reviewed and empirically carried out a meta-analysis on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 97 publications
5
33
0
Order By: Relevance
“…Although the correlation between impulsivity and compulsivity is substantially higher in the problematic than in the non-problematic group, group differences on these variables are non-significant. Contrary to this finding, some literature data suggested positive relationships between work addiction and impulsivity and obsessive-compulsivity (31,32). Further studies should select an assessment instrument that is better at predicting work addiction (i.e., validated with a clinical diagnosis).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Although the correlation between impulsivity and compulsivity is substantially higher in the problematic than in the non-problematic group, group differences on these variables are non-significant. Contrary to this finding, some literature data suggested positive relationships between work addiction and impulsivity and obsessive-compulsivity (31,32). Further studies should select an assessment instrument that is better at predicting work addiction (i.e., validated with a clinical diagnosis).…”
Section: Discussionmentioning
confidence: 80%
“…In line with these, numerous existing studies highlighted the possible risk role of impulsivity and compulsivity in various forms of behavioral addictions. Namely, higher levels of impulsivity and compulsivity were associated with increased rates of gaming disorder (21,22) problematic internet use (23,24), gambling disorder (25,26), exercise addiction (27,28), compulsive buying disorder (29,30), work addiction (31,32) and hair pulling disorder (33,34). However, it is important to note that there might be differences between behavioral addictions in their associations with impulsivity and compulsivity (e.g., impulsivity might have a greater exploratory role in gaming disorder than compulsivity, whereas in gambling disorder both impulsivity and compulsivity might have a significant impact) (1,35).…”
Section: Introductionmentioning
confidence: 99%
“…Akin to disordered gambling, it is possible that the same model may help explain other addictive behaviors, such as workaholism (Griffiths, 2005). A recent meta-analysis found a moderate association between perfectionism and workaholism and a small-to-moderate association between a work-focused self-concept and workaholism (Kun, Takacs, Richman, Griffiths, & Demetrovics, 2020). Future research can examine whether having a work-focused selfconcept (stemming from perfectionism) is associated with workaholism severity among people who have erroneous beliefs about maladaptive work strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses have identified associations between different addictions and the five-factor model. For instance, Kun et al (17) showed that openness and conscientiousness were positively related to work addiction, whereas Astarini and Yadiarso (18) found that of the fivefactor model's traits, conscientiousness, and agreeableness had the strongest, and inverse associations with internet addiction. Further, Marengop et al (19) reported that conscientiousness had the strongest and inverse association with smartphone use disorder and Hakulinen et al (20) showed that high scores on extroversion and low scores on conscientiousness were associated with heavy alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%